2010
DOI: 10.1177/1756283x10388682
|View full text |Cite
|
Sign up to set email alerts
|

The association of bile acid excretion and atherosclerotic coronary artery disease

Abstract: Abstract:Background: Excess cholesterol is usually eliminated from the body by conversion to bile acids excreted in feces as bile salts. The excretion of large amounts of bile protects against atherosclerosis, while diminished excretion may lead to coronary artery disease (CAD). Objective: To investigate a relationship between CAD and bile acid excretion. Methods: Bile acid excretion was compared between 36 patients with proven CAD and 37 CAD-free individuals (controls). The groups were comparable for demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 20 publications
3
57
1
Order By: Relevance
“…Gender specifi city of bile acid metabolic pathways has also been shown in Cyp7A1-defi cient mice, where attenuated BSEP and changes in gall bladder bile composition is only observed in female mice ( 33 ). Charach et al ( 34 ) described a strong correlation between bile acid secretion and coronary artery disease (CAD) in humans, where patients with established CAD excreted significantly lower amounts of bile acids, and concluded that impaired ability to excrete cholesterol may be an additional risk factor for CAD development. Additionally, while normal bile acid secretion in heterozygous familial hypercholesterolemic patients is not associated with CAD, suboptimal bile acid synthesis, especially in males, is strongly related to development of CAD ( 35 ).…”
Section: Fig 4 Plasma Lipoprotein Profi Les Ldlrmentioning
confidence: 98%
“…Gender specifi city of bile acid metabolic pathways has also been shown in Cyp7A1-defi cient mice, where attenuated BSEP and changes in gall bladder bile composition is only observed in female mice ( 33 ). Charach et al ( 34 ) described a strong correlation between bile acid secretion and coronary artery disease (CAD) in humans, where patients with established CAD excreted significantly lower amounts of bile acids, and concluded that impaired ability to excrete cholesterol may be an additional risk factor for CAD development. Additionally, while normal bile acid secretion in heterozygous familial hypercholesterolemic patients is not associated with CAD, suboptimal bile acid synthesis, especially in males, is strongly related to development of CAD ( 35 ).…”
Section: Fig 4 Plasma Lipoprotein Profi Les Ldlrmentioning
confidence: 98%
“…About 5 % of BA may pass to the distal ileum and colon where they undergo deconjugation by the gut microbiota reducing their absorbability and increasing their loss in faeces. Since BA synthesis from cholesterol is under tight control in the liver, BA lost in faeces must be replaced driving hepatic uptake and metabolism of circulating cholesterol (80,81) . Indeed, increased loss of BA or cholesterol in faeces has long been suggested as a mode of action of dietary fibres and whole-plant foods in lowering blood cholesterol (82)(83)(84) .…”
Section: An Anthropology Of Diet: Microbe Interactions Within the Hummentioning
confidence: 99%
“…We observed that liver-specific transgenic expression of human liver CEH enhanced flux of HDL-CE to bile and feces and reduced Western-diet induced atherosclerosis [1517]. Enhanced bile acid secretion was found to reduce the CVD risk [18, 19]. These studies validated the unidirectional flux of cholesterol from macrophage foam cells to liver and to bile/feces as an anti-atherogenic step.…”
Section: Introductionmentioning
confidence: 87%